2020
DOI: 10.1108/tr-02-2019-0050
|View full text |Cite
|
Sign up to set email alerts
|

Brand personality in cultural tourism through social media

Abstract: Purpose This study aims to analyze the effect of the use of social media on the perception of brand personality and to identify its effect on customer brand engagement. Design/methodology/approach The study adopted an exploratory approach, adapting Aaker's brand personality scale (1997) to the context of cultural tourism before carrying out a quantitative study resorting to a structural equation modeling to obtain empirical evidence to identify these relationships. Findings The findings reveal that the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 130 publications
1
12
0
Order By: Relevance
“…Social media has gained momentum in tourism marketing to gain insights into consumer experience (Gaffar et al , 2021; Peco-Torres et al , 2021). While analysing UGC on social media has become more commonplace in recent years, a strong focus is placed on Facebook, followed by YouTube and Twitter (Shawky et al , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Social media has gained momentum in tourism marketing to gain insights into consumer experience (Gaffar et al , 2021; Peco-Torres et al , 2021). While analysing UGC on social media has become more commonplace in recent years, a strong focus is placed on Facebook, followed by YouTube and Twitter (Shawky et al , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Destination personality is an important affective evaluation of the place and existing research has established that even in countries with cultural and physical proximity, such as countries in South America (Rojas-Méndez and Hine, 2017), Figure 1 Global tourism logos destinations may use social media (Bujosa et al, 2015;Peco-Torres et al, 2020) or their web sites (Rojas-Méndez and Hine, 2017) to project destination specific personality traits for their positioning amongst international tourists.…”
Section: Progress In Tourism and Hospitality Brand Managementmentioning
confidence: 99%
“…Even though Aaker's brand personality model has been widely used, it is not free from limitations (Peco-Torres et al, 2020). For example, Eisend and Stokburger-Sauer (2013) found that ruggedness and excitement were not strongly related to brand commitment and brand attitude.…”
Section: Jiabr 124mentioning
confidence: 99%